TESTING OF KAEMPFEROL CONTENT IN ETHANOL EXTRACT OF MELINJO SEEDS (GNETUM GNEMON L.) AND BAJAKAH ROOT (SPATHBOLOBUS LITTORALIS) USING THE IN SILICO METHOD AS A CANDIDATE FOR LUNG CANCER DRUG - Lusendra, Ghaniyya Putri (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
This research is about testing the antiviral activity of compounds contained in Melinjo seed (Gnetum gnemon L.) and Bajakah root (Spathbolobus littoralis) as an anti lung cancer drugs candidate using the in silico method. The purpose of this study was to determine the antiviral activity and interactions of the bioactive component that used in this study is kaempferol which has an anti cancer effect. The result of the Docking of the kaempferol compound and protein migration inhibitory factor machropages that do not have water or are clean. Bajakah root and melinjo seed contain kaempferol compound which are able to prevent or cure cancer, expecially in lung cancer patients. Kaempferol compound has antioxidant potential that works to counteract free radicals in the body, making it very suitable for use as a candidate for lung cancer drugs.